Control of bistability, oscillations and chaos in a model electrocatalytic process on a spherical electrode surface - O. I. Gichan (Хімія, фізика та технологія поверхні)
The role of a preceding chemical reaction in the appearance of three dynamical instabilities leading to multistability of steady states, periodic current oscillations, and possible chaotic behavior in a model electrocatalytic process on a spherical electrode surface under potentiostatic conditions has been determined. A class of non-equilibrium systems where these instabilities can arise was sketched out and possible applications of these instabilities were presented from recent literature data. The results obtained are actual and fruitful in context of nonlinear dynamics and can help to understand the processes at interfaces.